ANALISIS KEKUATAN RANGKA BATANG KOMPONEN MESIN PRESS KEMASAN MINUMAN LOGAM NON FERRO - Mikael Sean Hendito; Daniel Joachim; Harto Tanujaya; Sobron Yamin Lubis (POROS, 2021)
Beverage cans is a sheet coated of steel with tin (Sn). It is a steel sheet container coated with thin white tin that has a content value of 1.00% to 1.25% of the total weight of that can. The method used in this design is to make a truss design using special design software then determine the constituent materials and dimensions of the truss then do a strength analysis of the truss. The purpose of this design is to determine the maximum strength of the press machine truss that can be accepted with a certain force. This design starts from making a truss design with dimensions of length, width, and height are 260 mm, 100 mm, and 500 mm, respectively. The result obtained from this design are that the bending moment obtained is 43.8 MPa, the total moment of inertia is 38,286.9 mm4, the maximum stress in the truss is 23 MPa while the allowable stress according to the frame material made of Hollow iron is 124 MPa.